Biocidal action of combined agents based on polyhexamethylene guanidine - Грегірчак, Наталія Миколаївна (Technology audit and production reserves, 2013)
The paper gives the comparative evaluation of the effectiveness of the use of disinfectants of different chemical groups. It is noted that one of the most promising groups of disinfectants is polyhexamethylene guanidine (PHMG). To increase the effectiveness of its action it was proposed to create new combined biocidal agents based on PHMG with (NH4)2S2O8 and H2O2 and investigate their antimicrobial properties. Antimicrobial action of disinfectants based on polyhexamethylene guanidine salts in combination with hydrogen peroxide and ammonium persulphate was determined in relation to the test-cultures of microorganisms (Escherichia coli IEM-1, Bacillus subtilis TU-2, Staphylococcus aureus BMS-1, Candida albicans D-6, Aspergillus niger R-3). A comparative evaluation of combined biocides based on PHMG, (NH4)2S2O8 and H2O2 on bacterial, fungal microflora was conducted and minimum inhibitory and biocidal concentrations of these drugs were determined. This will allow the improvement of the efficiency of sanitization by combined disinfectants.